(untitled) (Altre Modernità, 2024)
The article presents a corpus of texts written in Italian by Latin American authors residing in Italy. More specifically, it includes, on the one hand, a selection of stories submitted for the Lingua Madre Literary Contest and, on the other, the ‘open letter—first published by the newspaper La Repubblica and later edited and published by the editorial People—by Elizabeth Arquinigo Pardo. In the proposed corpus, a common reflection on identity and belonging stands out, as well as the relevance of a gender perspective. The selected texts raise, in several cases, the existence of an identity or a third space-time, which recalls the category of in-between proposed by Chicana women writers, as well as the centrality of the maternal figure.